Neural Stem Cell Regulation by Adhesion Molecules Within the Subependymal Niche - Morante-Redolat, Jose Manuel; Porlan, Eva (Frontiers in Cell and Developmental Biology, 2019)
In the mammalian adult brain, neural stem cells persist in neurogenic niches. The subependymal zone is the most prolific neurogenic niche in adult rodents, where residing stem cells generate large numbers of immature neurons that migrate into the olfactory bulb, where they differentiate into different types of interneurons. Subependymal neural stem cells derive from embryonic radial glia and retain some of their features like apico-basal polarity, with apical processes piercing the ependymal layer, and a basal process contacting blood vessels, constituting an epithelial niche. Conservation of the cytoarchitecture of the niche is of crucial importance for the maintenance of stem cells and for their neurogenic potential. In this minireview we will focus on extracellular matrix and adhesion molecules in the adult subependymal zone, showing their involvement not only as structural elements sustaining the niche architecture and topology, but also in the maintenance of stemness and regulation of the quiescence-proliferation balance.